Investigation of Heat Treatment Processes Effects on Erosion Behavior of BOHLAR Steel K720 : التحقق من تأثير عمليات المعالجة الحرارية على سلوك الاهتراء لفولاذ بوهلر K720 - Abed Noufal Kasouha - Sami Nabil Antakli (Journal of engineering sciences and information technology, 2019)
This study aim to investigate from influence of heat treatment processes on erosion resistance of high carbon steel Bohler K720, where we got untreated plate of this steel with dimensions (500x60x10 mm), then cut it to specimens with dimensions (60x15x10 mm), and every group of these specimens was undergone to different heat treatment, heating to 810ºC, holding 10 min, then cooling in different mediums (water, oil, air), other groups of specimens that cooled in oil were tempered at temperatures (100,200,300,400 ºC) for 30 min, and by that we got eight groups including the as received specimen that differ on each other in heat treatments conditions. The microstructure was examined for each sample, and the hardness was measured, and erosion test was applied by use rubber wheel machine with preload and sand current. The results of tests showed that the water quenched specimens have the highest hardness 70HRC and the highest erosion resistance 0.14%, but the quenching in water caused cracks in specimens, while the cooling in air gave the lower hardness 59HRC and erosion rate 0.306%. For the specimens that quenched in oil and tempered, the results showed that with increasing the temperature of tempering from 100ºC to 400ºC the hardness decreasing from 64HRC to 50HRC and the erosion rate increased from 0.201% to 0.451. The summery that the quenching process which aim to obtain martensitic structure and cause internal stresses within structure because of cooling speed was by oil and gave high hardness and erosion values without cracks and fractures, and by tempering process which consider important to make the specimens more stable can re-control by these two values to suit the practical application by changing temperature.